Vibration control of a pneumatic driven piezoelectric flexible manipulator using self-organizing map based multiple models. (March 2016) - Zhao, Zhi-li; Qiu, Zhi-cheng; Zhang, Xian-min; Han, Jian-da
Abstract: A kind of hybrid pneumatic-piezoelectric flexible manipulator system has been presented in the paper. A hybrid driving scheme is achieved by combining of a pneumatic proportional valve based pneumatic drive and a piezoelectric actuator bonded to the flexible beam. The system dynamics models are obtained based on system identification approaches, using the established experimental system. For system identification of the flexible piezoelectric manipulator subsystem, parametric estimation methods are utilized. For the pneumatic driven system, a single global linear model is not accurate enough to describe its dynamics, due to the high nonlinearity of the pneumatic driven system. Therefore, a self-organizing map (SOM) based multi-model system identification approach is used to get multiple local linear models. Then, a SOM based multi-model inverse controller and a variable damping pole-placement controller are applied to the pneumatic drive and piezoelectric actuator, respectively. Experiments on pneumatic driven vibration control, piezoelectric vibration control and hybrid vibration control are conducted, utilized proportional and derivative (PD) control, SOM based multi-model inverse controller, and the variable damping pole-placement controller. Experimental results demonstrate that the investigated control algorithms can improve the vibration control performance of the pneumatic driven flexible piezoelectric manipulator system. Highlights: A hybrid driving scheme is composed of pneumatic and piezoelectric driving. Self-organizing map (SOM) based multi-model system identification approach is used. SOM based multi-model inverse controller is applied to the pneumatic drive system. Variable damping pole-placement controller is designed for piezoelectric control. Experiments are conducted to suppress the vibration of the flexible manipulator.